PENGARUH GAYA HIDUP CASHLESS, DAN LITERASI FINANSIAL TERHADAP PERILAKU KEUANGAN PENGGUNAAN QUICK RESPONSE CODE INDONESIAN STANDARD (QRIS) MELALUI PENGELOLAAN KEUANGAN SEBAGAI VARIABEL MEDIASI (Studi Kasus pada Gen Z di Kecamatan Karang Tengah, Kota Tanger - Chikal Wirdianti Mustafa; Rizki Pratomo Sunarwibowo (Jurnal Nirta : Inovasi Multidisiplin, 2026)
This study aims to analyze the influence of a cashless lifestyle and financial literacy on financial behavior, with financial management as a mediating variable among Generation Z users of the Quick Response Code Indonesian Standard (QRIS) in Karang Tengah District. This research applies a quantitative approach using an online questionnaire distributed to 400 respondents. Data were analyzed using Partial Least Square–Structural Equation Modeling (PLS-SEM) with the SmartPLS version 4.0.9.9 software. The results indicate that the cashless lifestyle, financial literacy, and financial management have a positive and significant effect on financial behavior. Furthermore, financial management was found to significantly mediate the relationship between cashless lifestyle and financial literacy on financial behavior. The R² value of 0.726 indicates that cashless lifestyle and financial literacy have a strong influence on the financial management of Generation Z in Karang Tengah District. This finding suggests that the majority of the variation in financial management among Generation Z in this area can be explained by the level of adoption of cashless payment systems and their understanding of financial concepts.